Mito e rito na Europa setentrional pré-cristã: investigando a caçada selvagem na poesia e prosa escandinava do séc. XII - XIV - Miranda, Pablo Gomes de (2021)
Our research goals are to analyze a set of myths that have as elements in common a march or a procession of fantastic beings, led by some figure of great political or religious importance, being preceded by terrifying visions. Known as the Wild Hunt, it was, above all, a group of folk narratives that became famous as such from the investigations of antiquaries including Jacob Grimm. Medieval documents about the Wild Hunt are of different natures: elegiac poems, Icelandic Sagas and chronicles, material that was written over a long period and that undoubtedly underwent several transformations in the process of transmitting its elements. There are mainly two large sets of sources: those belonging to a Latin Europe , which are mainly Christian and the other belonging to Northern Europe, in which the process of Christianization was late. Our objective is, after examining the sources and their components, to question the possibility that the visions of the dead warriors and their destiny in the afterlife are representations of some kind of rite performed by medieval Scandinavians.